Optimization of Uma Lengge Tourism Village Management - Rizqi Madani Albayyin (Future Tecno-Science Publisher, 2025)
The Independent Study Program Merdeka Belajar Kampus Merdeka aims to optimize the management of Uma Lengge Tourism Village in Maria Village, Wawo District, Bima Regency. Optimization is carried out through three main aspects, namely increasing village promotion, strengthening synergy between institutions, and responsiveness to tourist complaints. This program includes the creation of social media for digital promotion, increasing coordination between the village government, the Tourism Office, and Pokdarwis, and evaluating tourist complaints. The results of the program show increased digital village visibility, more integrated inter-institutional relationships, and improved services to tourists. Despite facing obstacles such as limited resources and community participation, this program has made a positive contribution to the management of tourist villages and increased student competence in the practical application of knowledge. Recommendations for the sustainability of the program include additional training for the community and managers and raising support from stakeholders.